NEW DRY GRASSLAND ASSOCIATIONS FROM THE AUSONI-AURUNCI MOUNTAINS (CENTRAL ITALY) – SYNTAXONOMICAL UPDATING AND DISCUSSION ON THE HIGHER RANK SYNTAXA - Di Pietro, Romeo (Hacquetia, 2015)
A phytosociological study on the most extensive dry grassland communities of the coastal limestone massif of the Ausoni-Aurunci mountains (southern Latium, central Italy) is here presented. Violo pseudogracilis-Koelerietum splendentis ass. nova is restricted to the montane belt of the Aurunci mountains where it is dynamically related to the mesophilous Ostrya carpinifolia or Fagus sylvatica woodlands. Helichryso italici-Brometum erecti ass. nova is found within the upper hilly and submontane belt of both the Ausoni mountains (typical aspect) and the Aurunci mountains (subassociation saturejetosum montanae), where it is dynamically related with termophilous Ostrya carpinifolia woods and mesophilous Quercus ilex woods. Helichryso-Brometum is differentiated from Violo- Koelerietum in that it has a higher incidence of the steno-Mediterranean therophytic component. As far as the higher rank syntaxa are concerned, in this study the following changes were made in accordance with the rules of ICPN: the name Phleo ambigui-Bromion erecti Biondi et al. 1995 was considered invalid due to the invalidity of its nomenclatural type Asperulo purpureae-Brometum erecti. In contrast, the validity of the old name Cytiso spinescentis- Bromion erecti Bonin 1978 was demonstrated and its nomenclatural type, Lavandulo-Asphodelinetum luteae Bonin 1978, was lectotypified. Thus Cytiso spinescenti-Bromion erecti Bonin 1978 henceforth substitutes Phleo ambigui- Bromion erecti (nom. inval.) as the syntaxonomical reference for the endemic alliance of the hilly and montane limestone dry grasslands of the central and southern Apennines. Cytiso-Bromion is here divided into two suballiances: Sideritidenion italicae Biondi et al. 1995, Phleo ambigui-Bromenion erecti Biondi et al. ex Di Pietro suball. nov. Cytiso-Bromion belong to the new suborder Festuco circummediterraneae-Seslerienalia nitidae (Ubaldi 2003) stat. nov. and to the order Artemisio albae-Brometalia erecti Ubaldi ex Mucina & Dengler 2009. New and updated packages of characteristic and differential species for both Cytiso spinescenti-Bromion erecti and its related suballiances are proposed. Furthermore the validity of the name Astragaletum calabrici Giacomini & Gentile ex Bonin 1978, was proved and the association lectotypified. This association, which was previously included in Cytiso-Bromion erecti, is moved into Koelerio brutiae-Astragalion calabrici. Finally some interesting coenological and syndynamical similarities with Scorzonero-Chrysopogonetalia western Dalmatia submediterranean dry pastures are discussed.